2015
DOI: 10.1089/humc.2015.076
|View full text |Cite|
|
Sign up to set email alerts
|

Safety and Biodistribution Evaluation in Cynomolgus Macaques of rAAV2tYF-CB-hRS1, a Recombinant Adeno-Associated Virus Vector Expressing Retinoschisin

Abstract: Applied Genetic Technologies Corporation is developing rAAV2tYF-CB-hRS1, a recombinant adenoassociated virus (rAAV) vector for treatment of X-linked retinoschisis (XLRS), an inherited retinal disease characterized by splitting (schisis) of retinal layers causing poor vision. We report here results of a study evaluating the safety and biodistribution of rAAV2tYF-CB-hRS1 in normal cynomolgus macaques. Three groups of male animals (n = 6 per group) received an intravitreal injection in one eye of either vehicle, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 34 publications
1
48
0
Order By: Relevance
“…The highest levels were in the animal euthanized on study day 5, which is consistent with other studies that have shown higher levels of vector DNA in animals euthanized 1 or 4 weeks after vector administration compared with animals euthanized 3 months after vector administration. 33,37,38 In other studies, dose-dependent restoration of cone photoreceptor function after subretinal injection of rAAV2tYF-PR1.7-hCNGB3 was demonstrated in CNGB3 knockout mice and CNGB3 mutant dogs. In the mouse model, cone ERG responses developed in 31% of eyes treated at a vector concentration of 1 · 10 12 VG/ml and 90% of eyes treated at a vector concentration of 4.2 · 10 12 VG/ ml.…”
Section: Evaluation Of Raav2tyf-pr17-hcngb3 In Macaquesmentioning
confidence: 84%
See 2 more Smart Citations
“…The highest levels were in the animal euthanized on study day 5, which is consistent with other studies that have shown higher levels of vector DNA in animals euthanized 1 or 4 weeks after vector administration compared with animals euthanized 3 months after vector administration. 33,37,38 In other studies, dose-dependent restoration of cone photoreceptor function after subretinal injection of rAAV2tYF-PR1.7-hCNGB3 was demonstrated in CNGB3 knockout mice and CNGB3 mutant dogs. In the mouse model, cone ERG responses developed in 31% of eyes treated at a vector concentration of 1 · 10 12 VG/ml and 90% of eyes treated at a vector concentration of 4.2 · 10 12 VG/ ml.…”
Section: Evaluation Of Raav2tyf-pr17-hcngb3 In Macaquesmentioning
confidence: 84%
“…32 The ocular inflammation observed in this study is similar to the ocular inflammation seen in nonhuman primates after intravitreal injection of rAAV2tYF-CB-hRS1, an AAV vector expressing retinoschisin (RS1) and packaged in AAV2tYF capsids. 33 Routine postoperative medication in this study consisted of topical atropine, antibiotics, and corticosteroids during the first 10 days after surgery and additional dilating and antiinflammatory medications at later time points, based on the clinical evaluation by the attending veterinarian. Previous studies in which humans received subretinal injections of AAV vector expressing RPE65 or REP1 employed a variety of postoperative dilating, antibiotic, and antiinflammatory regimens, including oral corticosteroids in some studies.…”
Section: Evaluation Of Raav2tyf-pr17-hcngb3 In Macaquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest levels were in the animal euthanized on study day 5, which is consistent with other studies that have shown higher levels of vector DNA in animals euthanized 1 or 4 weeks after vector administration compared with animals euthanized 3 months after vector administration. 33,37,38 In other studies, dose-dependent restoration of cone photoreceptor function after subretinal injection of rAAV2tYF-PR1.7-hCNGB3 was demonstrated in CNGB3 knockout mice and CNGB3 mutant dogs. In the mouse model, cone ERG responses developed in 31% of eyes treated at a vector concentration of 1 · 10 12 VG/ml and 90% of eyes treated at a vector concentration of 4.2 · 10 12 VG/ ml.…”
Section: Discussionmentioning
confidence: 84%
“…40 The method used to produce and purify rAAV 2tYF-PR1.7-hCNGB3 is the same as the method used for rAAV2tYF-CB-hRS1. 33 This method resulted in a product with purity >90% and low or undetectable levels of process residuals, similar to the low levels of process residuals seen in toxicology and clinical batches of an rAAV1-CB-hAAT product that had a favorable safety profile when administered by intramuscular injection in a clinical trial at doses up to 6 · 10 12 VG/kg (4.2 · 10 14 total VG in a 70-kg person) in subjects with a 1antitrypsin deficiency. 41,42 In conclusion, subretinal injection of rAAV2tYF-PR1.7-hCNGB3 at a concentration of 4 · 10 11 or 4 · 10 12 VG/ml was associated with a dose-related anterior and posterior segment inflammatory response that improved over time except that vitreous cells persisted longer than other manifestations of ocular inflammation.…”
Section: Discussionmentioning
confidence: 99%